THRIVING BEYOND CHANGE: FREQUENCY, SEVERITY, AND ASSOCIATION OF SYMPTOMS WITH CLINICO-DEMOGRAPHICS OF POSTMENOPAUSAL WOMEN OF KECH, TURBAT.: JPUMHS;2024:14:03,3-11.http://doi.org/10.46536/jpumhs/2024/14.03.528 - Yasmeen Gul1, Santosh Kumar Sidhwani2, Afzal Khaliq3, Nasrin Mumtaz4, Noman Sadiq5, Lareb Asad6 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
BACKGROUND: For women, the menopause is a normal and significant life transition, but it’s also commonly linked to stigmas and misconceptions. The major health problems that postmenopausal women encounter were to be identified, along with the knowledge, attitudes, and practices surrounding seeking medical attention for these problems, as well as the utilization pattern and any barriers to using these services. OBJECTIVE: To assess the knowledge, attitudes, practices, and healthcare seeking behavior of postmenopausal women regarding menopausal symptoms and associated health issues. METHODS: From March 2023 to March 2024, a cross-sectional study was carried out at the Turbat Teaching Hospital at KECH at the Department of Gynecology and Obstetrics. Following the acquisition of written informed consent, all postmenopausal women visiting the OPD were chosen one after the other. A pre-made survey was employed to assess the behavior of individuals seeking medical attention. In tables and graphs, the results were presented as percentages and frequencies. Where appropriate, the logistic regression analysis and chi-square test were used. A significance level of p ≤ 0.05 was deemed to exist. RESULTS: Participants in the study ranged in age from 40 to 80 years old, with a mean age of 61.47±8.28. 188 (29.1%) were from rural areas and 130 (40.9%) were residents from rural. Maximum patients were rom nuclear families who stays away from relatives 212 (66.7%) who smokes hookah 148 (46.5%) and eats gutka 12 (3.8%). Post-menopausal women had variety of symptoms to report as in current 270 (84.9%) of the women presented with joint pain and stiffness followed by vaginal dryness 262 (74.2%) and hair changes 258 (81.1%). Table: 01. While looking towards the attributes 246 (77.4%) of the women know or they heard about the process and physiology of menopause and they were aware about the process among them 172 (54.1%) felt comfortable to discuss the phenomenon and its related issues with their friends, fellows or peers. Majority of the participants were not taking the menopause as disease happened at old ages 238 (74.8%) while 228 (71.7%) thought that it makes women fat.CONCLUSION: Women around the world experience menopause differently due to a range of biological, psychological, social, and cultural factors that affect their views, values, and attitudes around menopause. The present study clearly shows that postmenopausal symptoms and other gynecological problems are very common in our study setting. Joint stiffness and pain were the most common menopausal symptoms in our study group, followed by vaginal dryness and irritation. Women from both urban and rural locations did not see menopause as an illness and had never thought to seek help from quacks or traditional healers when the characteristics were compared to the race.